Real‐Time Imaging of Ultrafast Charge Dynamics in Tetrafluoromethane from Attosecond Pump‐Probe Photoelectron Spectroscopy. Issue 46 (27th July 2018) - Plésiat, Etienne; Lara‐Astiaso, Manuel; Decleva, Piero; Palacios, Alicia; Martín, Fernando
Abstract: A pump‐probe experiment in the tetrafluoro‐methane (CF4 ) molecule has been theoretically simulated, allowing one to access electron dynamics in its natural time scale: the attosecond. The chosen pump and probe pulses can be currently produced in most attosecond laboratories. In this scheme, CF4 is first ionized by an extreme UV (XUV) attosecond pulse and the charge dynamics induced in the corresponding cation is probed with a few‐femtosecond visible light (VIS) pulse. We demonstrate that modulations in the calculated photoelectron spectra with the pump‐probe delay reflect the dynamics of the XUV‐induced electronic wave packet. In particular, from the analysis of these modulations in the interval of time delays where the pump and probe pulses do not overlap any more, one has access to the amplitudes and phases of the different components of the electronic wave packet generated by the attosecond pulse. These reflect a complex dynamics that basically consists of very fast charge fluctuations occurring all over the molecule without any preference for a particular molecular site. Abstract : Imagine all the charges : Electronic wave packet resulting from the interaction of tetrafluoromethane with a 150 attosecond extreme UV (XUV) pulse.